2012
DOI: 10.4028/www.scientific.net/amr.538-541.1746
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cryogenic Treatment on Grinding Residual Stress of WC-Co Cemented Carbides

Abstract: The changes in residual surface stress state significantly affect the mechanical behaviour of the materials. In this paper, the effect of cryogenic treatment on grinding residual stress of ultra-fine grained WC-Co hardmetals has been investigated by measuring the residual stress of ground carbide surfaces before and after cryogenic treatment. The results show that the cryogenic treatment can relieve the residual stresses of ground carbide surfaces. Relaxation degree of residual stresses is highly dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thermal residual stresses were induced due to thermal mismatch between the WC and the Co phase. A 20% reduction in residual stresses after CT execution was observed due to the cracking and plastic deformation in the WC grains [130].…”
Section: Cryogenic Application In Manufacturing Engineeringmentioning
confidence: 99%
“…Thermal residual stresses were induced due to thermal mismatch between the WC and the Co phase. A 20% reduction in residual stresses after CT execution was observed due to the cracking and plastic deformation in the WC grains [130].…”
Section: Cryogenic Application In Manufacturing Engineeringmentioning
confidence: 99%
“…The existing work has shown that the grinding-induce residual stress in the ground carbide materials is compressive in WC and tensile in Co (Hegeman, De Hosson, & De With, 2001;Yin et al, 2004), and it can be relieved effectively by annealing heat treatment (Yang, Odén, Johansson-Jõesaar, & Llanes, 2014). Relaxation degree of residual stresses can be defined as the relaxation rate, and it can be expressed as (Yuan & Xu, 2012):…”
Section: Effect Of Annealing Temperaturementioning
confidence: 99%
“…The results showed that: cryogenic treatment can make cemented carbide alloy phase atomic migration and rearrangement and tend to be uniformity, so as to improve high cobalt carbide phase composition, while can make the solid solution of W and C more uniform distribution, improving solid solution strengthening effects, thus significantly improve the bending strength of low cobalt magnetic carbide. Yuan, YG, etc [13] studied the effects of cryogenic treatment on WC-Co cemented carbide grinding residual stress. The results showed that: cryogenic treatment can reduce the residual stress on the surface of the cemented carbide.…”
Section: Cemented Carbide Cryogenic Treatment Of Domestic and Foreign...mentioning
confidence: 99%